Terahertz Detection by Asymmetric Dual Grating Gate Bilayer Graphene FETs with Integrated Bowtie Antenna - E. Abidi; A. Khan; J. A. Delgado-Notario; V. Clericó; J. Calvo-Gallego; T. Taniguchi; K. Watanabe; T. Otsuji; J. E. Velázquez; Y. M. Meziani (Nanomaterials, 2024)
An asymmetric dual-grating gate bilayer graphene-based field effect transistor (ADGG-GFET) with an integrated bowtie antenna was fabricated and its response as a Terahertz (THz) detector was experimentally investigated. The device was cooled down to 4.5 K, and excited at different frequencies (0.15, 0.3 and 0.6 THz) using a THz solid-state source. The integration of the bowtie antenna allowed to obtain a substantial increase in the photocurrent response (up to 8 nA) of the device at the three studied frequencies as compared to similar transistors lacking the integrated antenna (1 nA). The photocurrent increase was observed for all the studied values of the bias voltage applied to both the top and back gates. Besides the action of the antenna that helps the coupling of THz radiation to the transistor channel, the observed enhancement by nearly one order of magnitude of the photoresponse is also related to the modulation of the hole and electron concentration profiles inside the transistor channel by the bias voltages imposed to the top and back gates. The creation of local n and p regions leads to the formation of homojuctions (<semantics>np</semantics>, <semantics>pn</semantics> or <semantics>pp+</semantics>) along the channel that strongly affects the overall photoresponse of the detector. Additionally, the bias of both back and top gates could induce an opening of the gap of the bilayer graphene channel that would also contribute to the photocurrent.